2002
DOI: 10.1016/s0272-6963(02)00109-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of environmental management systems on corporate and environmental performance

Abstract: There has been an increase in interest towards corporate activities aimed at reducing or eliminating the waste created during the production, use and/or disposal of the firm's products. Prior research has focused on the need for such activities, while current research tries to identify those components that encourage or discourage such activities. As a result of the introduction of ISO 14001, attention has turned to corporate environmental management systems (EMS). The underlying assumption is that such a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
812
3
41

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,049 publications
(901 citation statements)
references
References 26 publications
45
812
3
41
Order By: Relevance
“…Our findings coincide with those derived from previous research (e.g. Annandale et al, 2004;Melnyk et al, 2003;Zhu and Sarkis, 2004). In fact, Wagner (2005) also demonstrates that high levels of environmental performance are only possible if a firm's environmental management has a proactive technological pollution orientation.…”
Section: Discussion and Managerial Implicationssupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings coincide with those derived from previous research (e.g. Annandale et al, 2004;Melnyk et al, 2003;Zhu and Sarkis, 2004). In fact, Wagner (2005) also demonstrates that high levels of environmental performance are only possible if a firm's environmental management has a proactive technological pollution orientation.…”
Section: Discussion and Managerial Implicationssupporting
confidence: 91%
“…Environmental management and environmental performance The environmental management literature has shown that the adoption of environmental practices by firms typically leads to or has to do with good environmental performance (e.g. Annandale et al, 2004;Melnyk et al, 2003;Zhu and Sarkis, 2004).…”
Section: Early Moving and Environmental Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The same kind of debate is repeated in the evaluation of the impacts of the ISO 14001 standard on improvements in environmental performance. While most studies tend to highlight the positive nature of these impacts and the fact that ISO 14001 certification improves environmental performance (Goh Eng et al, 2006;Melnyk et al, 2003;Potoski and Prakash, 2005;Pun and Hui, 2001;Standards Council of Canada, 2000), other studies question these benefits (Barla, 2007;Boiral, 2007;Christmann and Taylor, 2006;King et al, 2005;Welch et al, 2003).…”
Section: Introductionmentioning
confidence: 99%